Revisiting the Proportional Recovery Model in View of the Ceiling Effect of Fugl-Meyer Assessment. Issue 10 (17th June 2021) - Lee, Hyun Haeng; Kim, Deog Young; Sohn, Min Kyun; Shin, Yong-Il; Oh, Gyung-Jae; Lee, Yang-Soo; Joo, Min Cheol; Lee, So Young; Han, Junhee; Ahn, Jeonghoon; Chang, Won Hyuk; Kim, Ilyoel; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: The aim of this study was to verify the validity of the proportional recovery model in view of the ceiling effect of the Fugl-Meyer Assessment. Methods: We reviewed the medical records of patients enrolled in the Korean Stroke Cohort for Functioning and Rehabilitation between August 2012 and May 2015. Recovery proportion was defined as the actual change in Fugl-Meyer Assessment score of the upper extremity between 7 days and 6 months poststroke, relative to the initial neurological impairment. We then used logistic regression to identify clinical factors attributable to a ceiling effect of the Fugl-Meyer Assessment score of the upper extremity and propensity score matching to verify the validity of the proportional recovery rule. Results: We screened 10 636 patients and analyzed 849 patients (mean age, 65.4±11.9 years; female, 320 [37.7%]) with first-ever ischemic stroke. We found, through logistic regression analysis, that a one-unit increase in the initial neurological impairment and the age at stroke onset affected the odds ratio (1.0386 and 0.9736, respectively) of achieving the full Fugl-Meyer Assessment score of the upper limb at 6 months poststroke. We also demonstrated, through propensity score matching, that the difference in initial neurological impairment of the upper extremity resulted in discrepancy of the recovery proportion (0.92±0.20 [0–1] versus 0.81±0.31 [0–1], P <0.001). Conclusions: We demonstrated that the ceiling effect of the Fugl-Meyer Assessment score of the upper extremity is pronounced in patients with mild initial motor deficits of the upper extremity and that the recovery proportion varies according to the initial motor deficit of the upper limb using logistic regression analysis and propensity score matching, respectively. These results suggest that the proportional recovery model is not valid.